Immigrant-born workers and quality early childhood education and care in the Northern Territory, Australia. (4th May 2018) - Golebiowska, Kate; Boyle, Alicia; Pennec, Sophie; Horvath, Denise
Abstract: This paper focuses on the growing immigrant-born population of early childhood education and care (ECEC) workers in the Northern Territory of Australia, who represent a committed but poorly understood group within this workforce. The recent reforms to the ECEC workforce in Australia aim to achieve high-quality ECEC services by (a) growing this workforce size to meet the demand for services; (b) meeting the higher educator-to-children ratios; and (c) raising the overall level of qualifications of ECEC workers. By combining the statistical data in an innovative way, this paper shows that even when the growing numbers in this group are combined with newly qualified, immigrant-born and Australian-born entrants, the total number of workers may still be too small to fully implement recent reforms. It concludes by identifying data quality issues and future research directions that would help inform and develop a new strategy for the Northern Territory ECEC workforce.